KARAKTERISTIK KESEHATAN PERUSAHAAN DI INDUSTRI ASURANSI UMUM INDONESIA - Abrar Setiawan; Tony Irawan; Hendro Sasongko (Universitas Pakuan, 2020)
Health of general insurance companies can be seen from the value of Risk Based Capital (RBC) with a minimum value of 120%. In the 2013-2017 period, the RBC value tended to decline, 2 general insurance companies which had an RBC value of less than 120%, 1 company that is under the supervision of the regulator, and 1 company is bankrupt. 40 companies were used as samples. Based on descriptive statistical analysis, the average RBC of general insurance companies is 351%. This value is far higher than the minimum value set by the regulator, which is 120%. This RBC value that is too large means the general insurance company in Indonesia is at a healthy level. However, the RBC value that is too large also indicates that general insurance companies have not been able to maximize existing capital so that it is over the capital. The results of this study require management must also maintain the ideal RBC value so that the profits obtained remain optimal. The regulator must also keep an eye on the RBC value to stay greater than 120%. However, this RBC value should not be too large to prevent over capital so that there is a decrease in industrial performance.